Recent progress in analytical capillary isotachophoresis. Issue 1 (2nd August 2018) - Malá, Zdena; Gebauer, Petr
Abstract: This review brings a survey of studies on analytical ITP published since 2016 until the first quarter of 2018 and includes chapters about theory and principles, instrumentation and techniques, and analytical applications of ITP. It shows the position of analytical ITP among contemporary separation techniques, where particularly its unique concentrating capabilities keep the interest to include it into novel high‐sensitivity analytical procedures. The reviewed papers are considered according to their nature, techniques used, and instrumentation employed. The significance of electrolyte system composition is emphasized by providing explicit values where possible.